Do People Play Nash Equilibrium? Lessons From Evolutionary Game Theory - Mailath, George J. (Journal of Economic Literature, 1998)
Evolutionary game theory provides an answer to two of the central questions in economic modeling: when is it reasonable to assume that people are rational? And, when is it reasonable to assume that behavior is part of a Nash equilibrium (and if it is reasonable, which equilibrium)? The traditional answers are not compelling, and much of evolutionary modeling is motivated by the need for a better answer. Evolutionary game theory suggests that, in a range of settings, agents do (eventually) play a Nash equilibrium. Moreover, evolutionary modeling has shed light on the relative plausibility of different Nash equilibria.